Lichen endophyte derived pyridoxatin inactivates Candida growth by interfering with ergosterol biosynthesis - Chang, Wenqiang; Zhang, Ming; Li, Ying; Li, Xiaobin; Gao, Yanhui; Xie, Zhiyu; Lou, Hongxiang (Biochimica et biophysica acta, 2015)
This study is to characterize the antifungal effects of pyridoxatin (PYR), a small natural product isolated from an endolichenic fungus. The susceptibility tests in vitro and in vivo by using Caenorhabditis elegans as an infectious model were performed to evaluate the antifungal efficacy of PYR against Candida species. The cytotoxicity of PYR against normal human cells was tested using MTT assay. The transcriptional levels of genes related to sterol synthesis and cell cycle regulation were measured using real-time quantitative PCR (qPCR). The contents ergosterol, squalene, lanosterol were detected by liquid chromatography/tandem mass spectrometry (LC/MS). PYR was effective against four tested Candida species with its minimal inhibitory concentrations (MICs) ranging from 1–4μg/ml. No obvious cytotoxicity was observed for PYR against normal human cells. PYR inhibited the growth of Candida albicans, preventing the biofilm formation. And the antifungal action was independent on efflux pumps. The in vivo test showed PYR greatly prolonged the survival of infected C. elegans. qPCR results revealed that most of the genes related to sterol biosynthesis were considerably down-regulated in PYR-treated cells. Determination of the sterol content found that PYR inhibited the ergosterol synthesis dose dependently and caused the accumulation of squalene and lanosterol. Moreover, analysis of the structure–activity relationship revealed the heterocyclic hydroxamic acid in PYR was the key group for the antifungal action. PYR interferes with the ergosterol synthesis to exert antifungal action. The elucidated mechanism provides possible applications of PYR in fighting clinical relevant fungal infections. •Pyridoxatin harbors antifungal efficacy comparable with fluconazole.•Pyridoxatin greatly improved the survival of C. albicans infected C. elegans.•Pyridoxatin reduces the ergosterol content of C. albicans.•Heterocyclic hydroxamic acid acts as the functional group for pyridoxatin.